Entrepreneurship Development and Market Orientation to Improve The Performance of Creative Industry MSMEs in Sari Konveksi - Ariani, Ni Kadek Ayu; Ardani, Wayan; Widani, Ni Made (Implikasi: Jurnal Manajemen Sumber Daya Manusia, 2024)
Creative Industry is any process of creation, creativity, thoughts and ideas from a person or group which can then produce works or products afterwards. In this research, quantitative research methods are used, where this type of research uses research methods based on positivistic (concrete data), data. The research is in the form of numbers that will be measured using statistics as a calculation test tool. The research was carried out at Sari Konveksi which operates in the clothing manufacturing convection sector with the population used being 100 VVIP consumers and the samples taken were 50 people who were VVIP customers from Sari Konveksi, data collection was carried out by interviews, questionnaires and documentation so that the analysis technique used was multiple linear regression analysis and the results of this research showed that entrepreneurial development had a positive and significant effect on the performance of Sari Konveksi MSMEs and market orientation had a positive and significant effect on performance. With this research, Sari Konveksi MSMEs can carry out and develop entrepreneurship and market orientation in improving the performance of MSMEs, especially in the creative industries. Apart from that, entrepreneurial factors and market orientation really need to be developed for MSME owners so they can compete in the world of convection. This data can be used as a reference for future decision making.